PENDAMPINGAN HUKUM TERHADAP TERDAKWAH KASUS PENCURIAN DI PENGADILAN NEGERI WONOGIRI - Ainun Najib; Teguh Anshori; Aditya Fajri Kurnia Pradana (AL HAZIQ: Journal of Community Service, 2026)
Limited legal literacy among criminal defendants remains a significant challenge to ensuring procedural justice in Indonesia's criminal justice system. This community service project addresses this issue by providing direct legal assistance to a defendant in a motorcycle theft case, emphasizing the protection of procedural rights and the realization of a fair trial. The program employed courtroom legal representation, legal consultation, and case analysis based on judicial documents and trial proceedings. The findings reveal three major issues: defendants' inadequate understanding of criminal procedures and legal rights, excessive reliance on legal counsel without meaningful participation in their defense, and the persistence of a formalistic judicial approach that prioritizes conviction over legal education and rehabilitation. The novelty of this project lies in positioning legal aid as a legal empowerment strategy rather than merely courtroom representation. Its contribution demonstrates that integrating legal assistance with legal literacy enhances defendants' legal awareness, strengthens access to justice, and promotes a more rights-based criminal justice system.